High school teachers’ readiness for the implementation of Merdeka curriculum in English language teaching - Kaluge, Teresa Angelina; Usmi, Usmi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
Curriculum influences the approaches to teaching and learning foreign languages. The newly introduced Merdeka Curriculum in Indonesia has not been implemented by all high schools yet. The readiness of foreign language teachers was one of the influential factors for the school acceptance of the new curriculum. This study examined the readiness of foreign language teachers from high schools that have not yet implemented the Merdeka Curriculum. Data were obtained through questionnaires which were distributed to the English teachers and other subject teachers from several high schools in Indonesia. The results showed that there were two main dimensions that influenced the teacher readiness; the first is several changes that must be implemented and second, the negative attitudes towards the new curriculum. It is hoped that the results of this study can contribute as a support to enhance teachers’ positive attitude to ensure the implementation of the new curriculum. Kesiapan pengajar SMA terhadap pengajaran bahasa Inggris dalam kurikulum Merdeka Kurikulum berpengaruh terhadap pendekatan pengajaran dan pembelajaran bahasa asing. Kurikulum Merdeka yang belum lama ini diterapkan di Indonesia belum diterapkan oleh seluruh sekolah menengah atas. Kesiapan pengajar bahasa asing berpengaruh terhadap penerimaan sekolah terhadap kurikulum baru tersebut. Penelitian ini mengkaji kesiapan guru bahasa asing dari SMA yang belum menerapkan kurikulum Merdeka. Data diperoleh melalui kuesioner yang disebarkan kepada guru bahasa Inggris dan guru bahasa asing lainnya dari beberapa SMA/SMK di Indonesia. Hasil menunjukkan dua dimensi utama yang berpengaruh terhadap kesiapan guru, yaitu perubahan yang harus diberlakukan dan sikap negatif terhadap kurikulum yang baru. Diharapkan hasil penelitian ini berkontribusi sebagai masukan perlunya sikap positif guru sebagai pendukung implementasi kurikulum yang baru.